Shockproof how to hardwire your business for lasting success - Jacobs, Debra. (Wiley, 2011)
"You survived the recession . . . are you ready for what's next? With rapid developments and shifts in the economy, technology, and customer expectations, businesses - even those that are widely regarded as successful - are often only one shock away from failure. Leaders spend countless hours trying to derive the perfect business strategy or organization design, only to be thrown off kilter by an unanticipated change. When faced with a crisis that puts a business in peril, some leaders make the mistake of turning to "quick fix" solutions, such as downsizing, divestiture, hiring a "savior" leader, or over-investing in the latest flavor-of-the month management consulting fad. Long term success does not happen by accident. It happens when leaders are able to see what is going on in their businesses with absolute clarity and act with courage to ensure alignment between their business strategy, organization and talent. These leaders realize that by balancing focus and flexibility they can better prepare their businesses to respond to - or better yet, anticipate - change. As you navigate the changes and challenges of the future, let Shockproof guide your efforts to deliver lasting success in good times and bad."--